Extraction and characterization of sodium alginate from native Malaysian brown seaweed Sargassum polycystum - Alallam, Batoul; Abd Kadir, Erazuliana; Dewi, Firli Rahmah Primula; Yong, Yoke Keong; Lim, Vuanghao (Elsevier, 2025)
Malaysian seaweed, particularly Sargassum polycystum, has potential for alginate production, yet an extraction protocol for this seaweed remains lacking. This study aimed to optimize the extraction process to maximize alginate yield while characterizing the physicochemical properties of the extracted alginate and its potential applications. An alkali-based extraction method was employed, with key parameters, including alkali concentration, extraction temperature, and time, carefully optimized to yield 30.17 ± 0.76 % (g alginate/100 g dry seaweed biomass) of alginate. Sodium alginate extracted from Sargassum polycystum has a viscosity-average molecular weight of 4.73 ± 0.001 × 104 g/mol and an M/G ratio of 2.87. The physicochemical properties and biochemical composition of the extracted alginate revealed its capacity to be utilized as a natural antioxidant. An alginate-based nanohybrid for polyphenol delivery was developed to explore the potential applications of extracted alginate. This nanohybrid showed favorable properties (hydrodynamic particle size: 415 nm, PDI: 0.3, zeta potential: –44.7 mV), high encapsulation (80.13 %), and loading efficiency (19.21 ± 1.69 %). Alginate coating on the nanohybrid protected polyphenol from premature release, significantly enhancing its antioxidant activity. These findings suggest that alginate extracted from Malaysian Sargassum polycystum could be a valuable natural material for developing controlled-release delivery systems.